Local Development Management at the Example of the Sustainable Urban Mobility Plan - Przybyłowski, Adam (Regional Barometer. Analyses & Prognoses, 2016)
Urban transport system’s efficiency and capacity is one of the most important competitiveness factors. Sustainable mobility is one that meets the needs of society to move freely, gain access, communicate, trade and establish relationships without sacrificing other essential human or ecological requirements today or in the future. This concept should become a priority while planning the cities development nowadays. The aim of the paper is to present the basic idea and solutions as far as the promotion and implementation of this concept is concerned. Based on the available documents and data and also survey research, the paper presents sustainable mobility in agglomerations with a special emphasis on Gdynia.